ANTI-CORRUPTION STRATEGY AS AN ELEMENT OF STATE POLICY IN THE FIELD OF CUSTOMS ADMINISTRATION - Zinchenko, Anastasiia; Nechayeva, Iryna (Public Management and Policy, 2025)
The article examines the anti-corruption strategy as an element of state policy in the field of customs administration and as a set of preventive measures to reduce corruption risks in public administration sectors that are most favourable to such risks. The relevance of the topic is because customs authorities simultaneously perform fiscal, regulatory and control functions, which creates increased discretion of management decisions and, accordingly, favourable conditions for corruption and corruption-related offenses. The purpose of the study is to clarify the content of the anti-corruption strategy as an element of state policy, determine the features of its implementation in the customs sector and form priority areas for improving anti-corruption mechanisms within the framework of the current Anti-Corruption Strategy of Ukraine for 2021–2025. The results of the study show that the strategic approach to combating corruption in customs administration is currently being implemented through a combination of regulatory, institutional and digital solutions: the development of a “Single Window for International Trade”, risk-based control, internal anti-corruption control and staff training. At the same time, systemic problems remain: excessive discretionary powers, non-transparency of certain procedures (classification of goods, determination of customs value, appointment of inspections), personnel instability, as well as the need for measurable indicators of the effectiveness of anti-corruption measures. A separate role is played by international standards (the UN Convention against Corruption, GRECO recommendations, the Revised WMO Arusha Declaration), which set guidelines for the introduction of integrity, transparency and automation of customs processes. The conclusions are that the effectiveness of the anti-corruption strategy in the field of customs administration is determined by the complexity of the policy and can be increased through digitalization, reducing contacts of officials with foreign trade entities, transparency of decisions, strengthening internal control by authorized units, as well as through the development of an anti-corruption culture. Priority areas for further improvement are proposed: reducing discretion by introducing full digitalization of customs procedures, improving the regulatory framework, strengthening international cooperation, establishing mechanisms for interaction between structural units, strengthening the level of integrity.